SISTEM INFORMASI GEOGRAFIS (SIG) GUNA PEMETAAN CAKUPAN LAYANAN PADA PUSKESMAS SRONDOL SEMARANG - Arif Kurniadi (VISIKES: Jurnal Kesehatan Masyarakat, 2011)
Background:Manual system still used for out-patient registration in Puskesmas Srondol. Although, they already has Public Health Management Information System (called SIMPUS), but it was not work efficiently. The data of registration was doing manually by staff in registration. It only showed the number of visitors every week by payment type, patient status and policlinic. The information could not give more information for management to monitoring ofvisitors. So, it shall very useful using Geographic Information System (GIS) to make the data more informative and easier for management to making decision.Method: The research has aimed to map the out-patient registration by using Geographic Information System. This is a descriptive research.Result: Registration data started from the patient gave their identity family card to register the medical service. Then the officers make a note of service in register book. The patient will accept a ticket and queue number to get the medical service. Finally, recipe should be taken in dispensary and the status card back to the register officer. The officer has role to make the report weekly. Developing information system in registration must be based onvision, mission, function and objective the institution, i.e. Puskesmas Srondol. The system should be gave more information to help the management in solve the problem. By using the Windows 98 and Microsoft Visual FoxPro and Arc View, the registration data mapped to become more informative.Key Word : Geographic Information System, Registration